Pemanfaatan Limbah Umum Bahan Praktikum Tulang Ikan Parang-Parang (Chirocentrus Dorab) Sebagai Snack Kerupuk Berdasarkan Sifat Fisik Dan Organoleptik: Alternatif Snack Pencegah Stunting - Ambar Wicaksono; Eri Virmando; Retno Febrianti (Universitas Pahlawan Tuanku Tambusai, 2023)
Industrial processing of fish products leaves behind 35% of waste, including fish bone waste (Irawan in Ramdany et al., 1995). Fish bones can be made into flour with rich mineral content, especially calciuum. The fish bone flour can be used to make snacks that are commonly consumed by the consumers. One of the processed products that can be made from fish bone meal is crackers. The aim of this research was to determine the physical and organoleptic properties; as well as the proximate and calcium content of crackers made from Parang-parang (Chirocentrus dorab) fish bones. The research method used an experimental design. This research was carried out from March 2023 to November 2023. The proximate content test in fish bone crackers was carried out in the laboratory and the analysis was carried out using the T test at ?=0.05. The test results on the physical and organoleptic properties of Parang-parang fish bone crackers as a whole, the panel gave Formula-1 a favourable score with an average score of 3.8, while formulas 2 and 3 were depicted as normal with an average score of 3.06 and 3.22. The proximate and calcium test results for Formula-3 were higher than Formulas-1 and Formula-2.